Technological progress and the availability of European oil and gas resources - Aguilera, Roberto F.; Ripple, Ronald (Elsevier, 2012)
This paper estimates supply cost curves for conventional oil and gas in Europe. Oil and gas volumes are distributed across five categories that are based on production costs. The resulting supply figures are intended to be long term representations of how quantities vary with production costs. Both economic and physical measures are used since each provides practical information with respect to the concerns some energy commentators have expressed about oil and gas scarcity in the near future. Supply cost curves incorporating the effect of annual technological advancement (i.e. productivity gains) on production costs to the year 2030 are also estimated. On the quantity side, the curves include volumes from geological provinces not previously assessed. Results indicate that conventional oil and gas in Europe is abundant and can likely be produced at costs below current and projected market oil and gas prices.